Lipid nanocarriers loaded with natural compounds: Potential new therapies for age related neurodegenerative diseases?. (September 2018) - Soares, Telma Bezerra; Loureiro, Luís; Carvalho, Ana; Oliveira, Maria Elisabete C.D. Real; Dias, Alberto; Sarmento, Bruno; Lúcio, Marlene
Highlights: Age related neurodegenerative disorders (ARND) are the most debilitating and challenging diseases associated with the CNS. Lipid nanocarriers enclosing natural compounds are able to cross the blood brain barrier (BBB) being promising ARND therapies. The therapeutic benefits of the natural compounds are presented, as well as their possible mode of action in ARND. Nanocarriers' designing strategies aiming to enhance compounds bioavailability and pharmacokinetic profile are discussed. Targeting strategies used to overcome BBB and strategies used to trigger the release of compounds are also systematically discussed. Abstract: Age related neurodegenerative disorders (ARND) are presented as the most debilitating and challenging diseases associated with the central nervous system. Despite the advent of active molecules with a positive role on neurodegenerative mechanisms, many of the current therapeutic strategies remain ineffective in treating or preventing ARND. Lipid nanocarriers have emerged as efficient delivery systems with the capability to cross biological barriers, especially the blood brain barrier (BBB). Also, when associated to natural compounds, lipid nanocarriers have demonstrated to be an interesting alternative to ARND therapies with multiple beneficial effects. This comprehensive review focus on state-of-the-art lipid based nanocarriers for the delivery of natural compounds targeting neurodegeneration. A critical analysis of published reports will be also provided giving indications to researchers about the most promising ARND nanotherapy strategies.